Geo - location by proxy : approaching VGI from the perspective of geographic context :Powerpoint - Verplanke, J.J. (University of Twente, 2020)
This lecture presents: VGI is playing a role in providing location and context of problems; Reuse of VGI is a common source of information in disaster response and crowd control; VGI describes a place with an event; The attributes of the VGI combined with the contextual content provide a location.